Evolution of bimodal accretion flows - Gracia, J.; Peitz, J.; Keller, Ch; Camenzind, M. (Monthly notices of the Royal Astronomical Society, 2003)
We consider time-dependent models for rotating accretion flows on to black holes, where a transition takes place from an outer cooling-dominated disc to a radiatively inefficient flow in the inner region. In order to allow for a transition of this type we solve the energy equation, both for the gas and for the radiation field, including a radiative cooling flux and a turbulent convective heat flux directed along the negative entropy gradient. The transition region is found to be highly variable, and a corresponding variation is expected for the associated total luminosity. In particular, rapid oscillations of the transition radius are present on a time-scale comparable with the local Keplerian rotation time. These oscillations are accompanied by a quasi-periodic modulation of the mass flux at the outer edge of the advection-dominated accretion flow (ADAF). We speculate about the relevance for the high-frequency quasi-periodic oscillation phenomenon.